Comparing the efficacy of 3D-printing-assisted surgery with traditional surgical treatment of fracture: an umbrella review - Lin Xiao; Peiyuan Tang; Shengwu Yang; Jingyue Su; Wenbo Ma; Han Tan; Ying Zhu; Wenfeng Xiao; Ting Wen; Yusheng Li; Shuguang Liu; Zhenhan Deng (Journal of Orthopaedics and Traumatology)
Abstract Background The objective of this review is to evaluate the methodological quality of meta-analyses and observe the consistency of the evidence they generated to provide comprehensive and reliable evidence for the clinical use of three-dimensional (3D) printing in surgical treatment of fracture. Methods We searched three databases (PubMed, Embase, and Web of Science) up until August 2024. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards were adhered to in this review. The Measurement Tool to Assess Systematic Reviews (AMSTAR) 2 was used to rate the quality and reliability of the meta-analyses (MAs), and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to grade the outcomes. Furthermore, Graphical Representation of Overlap for Overviews (GROOVE) was employed to examine overlap, and the resulting evidence was categorized into four groups according to established criteria for evidence classification. Results Results from 14 meta-analyses were combined. AMSTAR 2 gave six meta-analyses a high rating, six MAs a moderate rating, and two MAs a low rating. Three-dimensional printing shows promising results in fracture surgical treatment, significantly reducing operation time and loss of blood for tibial plateau fracture. For acetabular fracture, apart from the positive effects on operation time (ratio of mean (ROM) = 0.74, 95% confidence interval (CI), 0.66–0.83, I 2 = 93%) and blood loss (ROM = 0.71, 95% CI 0.63–0.81, I 2 = 71%), 3D printing helps reduce postoperative complications (odds ratio (OR) = 0.42, 95% CI, 0.22–0.78, I 2 = 9%). For proximal humerus fracture, 3D printing helps shorten operation time (weighted mean difference (WMD) = −19.49; 95% CI −26.95 to −12.03; p < 0.05; I 2 = 91%), reduce blood loss (WMD = −46.49; 95% CI -76.01 to −16.97; p < 0.05; I 2 = 98%), and get higher Neer score that includes evaluation of pain, function, range of motion, and anatomical positioning (WMD = 9.57; 95% CI 8.11 to 11.04; p < 0.05; I 2 = 64%). Additionally, positive results are also indicated for other fractures, especially for operation time, blood loss, and postoperative complications. Conclusions Compared with traditional fracture surgical treatment, 3D-printing-assisted surgery has significant advantages and great effectiveness in terms of operation time, loss of blood, and postoperative complications in the treatment of many different types of fractures, with less harm to patients.